Neopetrosia de Laubenfels, 1949 from Brazil: description of a new species and a review of records (Haplosclerida: Demospongiae: Porifera) - Santos, George Garcia; Sandes, Joana; Cabral, Abigail; Pinheiro, Ulisses (Zootaxa, 2016)
The genus Neopetrosia was characterized by has fine brushes of oxeas issued from subectosomal tracts and compact choanosomal network. We report and describe here specimens collected in the coast of Brazil: Neopetrosia sulcata sp. nov. and Neopetrosia proxima. The first was previously recorded from Brazil as Neopetrosia proxima, but it was found that these specimens corresponded to a new species. Thus, we provide here the characterization of N. proxima from Brazilian coast. A taxonomic study of Brazilian samples is given, including description, illustrations and geographic distribution, combined with the comparison of the new species with all other descriptions of Neopetrosia from Atlantic.